Words that Wound and Laws that Silence: Offence, Harm, and Legal Limits on Discriminatory Expression - Sangiuliano, Anthony; Friedman, Mark (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2025)
This article analyzes when expression is discriminatory and when discriminatory expression should be legally prohibited. It reaches theoretical conclusions about these matters by examining the recent Ward v. Quebec (Commission des droits de la personne et des droits de la jeunesse) judgment of the Supreme Court of Canada. In Ward, the Court determined that a comedian’s jokes that ridiculed the appearance of a disabled boy did not constitute discriminatory expression because of disability. In any event, there was no reason to prohibit them under Quebec’s Charter of Human Rights and Freedoms that could outweigh the countervailing reason to protect the comedian’s freedom of expression. We argue that there are two weaknesses in the Court’s opinion. First, the Court adopted a conception of how to define expression as discriminatory expression that is inconsistent with standard approaches to this issue in law and the philosophical literature on the ethics of antidiscrimination. Second, while the Court held that only the imperative to prevent harm gives a reason to prohibit discriminatory expression, as opposed to preventing offence, it relied on an impoverished conception of harm that was restricted to the societal harm of hate speech. There are reasons to prohibit discriminatory expression to prevent other types of harms.